ANTICIPATION OF THE COMPONENTS OF PHRASEOLOGICAL UNITS - Jabbarova, Anora (Журнал иностранных языков и лингвистики, 2021)
This article is about anticipation of the components of phraseological units. It analyzes the essence of achieving stylistic and artistic effect. It should be born in mind that in such cases, the perception of a phraseological unit is carried out if the reader is familiar with the image of the original phraseological unit, which is implicit in the description